(untitled) (Revista Brasileira de Contabilidade e Gestão, 2021)
The themes of work ability and employability have evolved considerably in recent years, changing people’s role in the search for their professional careers. Thus, both young people and adults need to rethink how to overcome the deficiencies arising from the contemporary world’s transformations that require a constant mutation of what is considered professional skills. The purpose of this study aims to understand the relationship between workability factors and the implications of COVID- 19 at work. The research is classified as exploratory, and the method applied is considered a survey type survey. It uses intentional non-probabilistic sampling, using the questionnaire as a research tool. The questionnaire was applied to a sample of 87 respondents in the year 2020 at an employment agency of the national employment system. Data processing and analysis were carried out in two stages: a descriptive and exploratory analysis. Work ability is a concept little explored but of great relevance for disseminating knowledge regarding techniques for diversifying the potential of human work. It was observed that the sample could perceive the importance of developing their skills and that adaptations are necessary. However, reaching the foundations of employability is the first step towards constructing the development of workability. In this pandemic moment, factors such as admissions, dismissals, unemployment, working conditions and factors that hinder work execution have directly implicated in the establishment of jobs of work ability factors.